2020
DOI: 10.1038/s41598-020-61034-x
|View full text |Cite
|
Sign up to set email alerts
|

A new multigene HCIQ subfamily from the sea anemone Heteractis crispa encodes Kunitz-peptides exhibiting neuroprotective activity against 6-hydroxydopamine

Abstract: the Kunitz/Bpti-type peptides are ubiquitous in numerous organisms including marine venomous animals. the peptides demonstrate various biological activities and therefore they are the subject of a number of investigations. We have discovered a new HciQ subfamily belonging to recently described multigene HcGS family of Heteractis crispa Kunitz-peptides. the uniqueness of this subfamily is that the HciQ precursors contain a propeptide terminating in Lys-Arg (endopeptidase cleavage site) the same as in the neuro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…The Kunitz-type IQ-peptide HMIQ3c1, extracted from the venom of Heteractis magnifica , has shown neuroprotective activity, which may find application in the treatment of neurodegenerative diseases, such as Alzheimer’s [ 138 ]. Another Kunitz-type proteinase inhibitor that may support the treatment of Parkinson disease is HCIQ2c1 extracted from Heteractis crispa [ 121 ]. This study shows for the first time that Kunitz-peptides significantly increase neuroblastoma cell viability in an in vitro 6- hydroxydopamine-induced neurotoxicity model of Parkinson’s disease [ 121 ].…”
Section: Venoms Of Cnidariamentioning
confidence: 99%
See 1 more Smart Citation
“…The Kunitz-type IQ-peptide HMIQ3c1, extracted from the venom of Heteractis magnifica , has shown neuroprotective activity, which may find application in the treatment of neurodegenerative diseases, such as Alzheimer’s [ 138 ]. Another Kunitz-type proteinase inhibitor that may support the treatment of Parkinson disease is HCIQ2c1 extracted from Heteractis crispa [ 121 ]. This study shows for the first time that Kunitz-peptides significantly increase neuroblastoma cell viability in an in vitro 6- hydroxydopamine-induced neurotoxicity model of Parkinson’s disease [ 121 ].…”
Section: Venoms Of Cnidariamentioning
confidence: 99%
“…Another Kunitz-type proteinase inhibitor that may support the treatment of Parkinson disease is HCIQ2c1 extracted from Heteractis crispa [ 121 ]. This study shows for the first time that Kunitz-peptides significantly increase neuroblastoma cell viability in an in vitro 6- hydroxydopamine-induced neurotoxicity model of Parkinson’s disease [ 121 ].…”
Section: Venoms Of Cnidariamentioning
confidence: 99%
“…Moreover, these peptides contain conserved amino acids at the N-and C-termini. Besides trypsin, Kunitz-type peptides from sea anemone H. crispa are also able to interact with other serine proteases (chymotrypsin, elastase, kallikrein) [19,39,53], modulate or block TRPV1 channel [22][23][24], revealing different kind of biological effects such as analgesic [22,[54][55][56], anti-inflammatory [9,41,54,57], antihistamine [41,58], as well as neuroprotective activity [59,60]. However, despite their high degree of homology with the known bifunctional peptides, like kalicludines, SHTXIII, APEKTx1, and ShPI-1 [16,18,19], none of them has shown potassium channels blocking activity.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a novel Kunitz-like peptide (PcKuz3) has been identified from Palythoa caribaeorum, as a neuroprotective agent providing an opportunity to develop a treatment for neurodegenerative diseases (Liao et al 2019). According to a latest research, another type of kunitz peptide was reported that exhibit neuroprotective activity against 6-hydroxydopamine (Kvetkina et al 2020).…”
Section: Bioactivities Of Cnidarian Toxinsmentioning
confidence: 99%